Hippotherapy Through the Eyes of the Riding Coach - Ali Ekber Ün (Turkish Journal of Agriculture: Food Science and Technology, 2020)
The purpose of this review article is to collaborate on future studies about hippotherapy to horse and riding trainers, health professionals, veterinarians, individuals in need and individuals with disabilities and their relatives and to shed light on academic studies. It has been stated in studies that hippotherapy is beneficial for patients in the world. Therefore, as a result of new private hippotherapy centers in public institutions and in Turkey, studies on hippotherapy have been started. The studies carried out in hippotherapy are increasing and widespread and continuing to contribute to the treatment of the individuals in need and individuals with disabilities with hippotherapy sessions with expert teams. However, in the studies, the sessions of the hippotherapy team with two common creatures have great duties on the equestrian coaches in order to meet the needs of the horse and the individual in need or individual with disability. For this reason, since hippotherapy is a multidisciplinary team work consisting of specialist professionals, it has been researched to contribute to the horse and rider coaches on the field and to the expert team attending the sessions, to the new experts and the families of the individuals in need and disabled individuals. In the current review, the information about the history of hippotherapy and development, information about hippotherapy institutions in Turkey, individuals in need and individuals with disabilities, benefits of hippotherapy, characteristics of the hippotherapy horse, training of the hippotherapy horse are emphasized, and especially emphasis is placed on the use of work in the field of horse and equestrian coaching.